2016
DOI: 10.1016/j.physa.2015.12.163
|View full text |Cite
|
Sign up to set email alerts
|

Non performing loans (NPLs) in a crisis economy: Long-run equilibrium analysis with a real time VEC model for Greece (2001–2015)

Abstract: Αs a result of domestic and international factors, the Greek economy faced a severe crisis which is directly comparable only to the Great Recession. In this context, a prominent victim of this situation was the country"s banking system. This paper attempts to shed light on the determining factors of non-performing loans in the Greek banking sector. The analysis presents empirical evidence from the Greek economy, using aggregate data on a quarterly basis, in the time period 2001-2015, fully capturing the recent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 34 publications
3
41
0
3
Order By: Relevance
“…Beck et al (2015) used a number of national samples to analyze the influence of macroeconomic factors on non-performing loans, and found that real GDP growth, stock prices, exchange rates, and interest rates greatly decrease the scale of non-performing loans, while the negative effect of the stock is stronger in developed countries [20]. Konstantakis et al (2016) used the characteristics of the economic crisis to analyze the determinants of non-performing loans, and pointed out that macroeconomic factors and financial factors could significantly change the scale of banks' non-performing loans [21]. According to the macroeconomic analysis, some indicators of the regional economy and the financial market provide a certain relationship with the non-performing loans.…”
Section: Non-performing Loansmentioning
confidence: 99%
“…Beck et al (2015) used a number of national samples to analyze the influence of macroeconomic factors on non-performing loans, and found that real GDP growth, stock prices, exchange rates, and interest rates greatly decrease the scale of non-performing loans, while the negative effect of the stock is stronger in developed countries [20]. Konstantakis et al (2016) used the characteristics of the economic crisis to analyze the determinants of non-performing loans, and pointed out that macroeconomic factors and financial factors could significantly change the scale of banks' non-performing loans [21]. According to the macroeconomic analysis, some indicators of the regional economy and the financial market provide a certain relationship with the non-performing loans.…”
Section: Non-performing Loansmentioning
confidence: 99%
“…There are many studies focusing on the problem of the default rate of loans in the banking sector, most of which are focused on the relationship between macroeconomic determinants and NPLs [4][5][6]. A number of studies are devoted to the fact that the effect of macroeconomic conditions on the level of non-performing loans can be significant [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…NPLs are positively correlated to unemployment, whereas they are negatively correlated to GDP growth rate and inflation [49]. Furthermore, NPLs are positively correlated to macroeconomic and financial disequilibriums, as well as to the government's fund-raising capacity [50]. Figure 2 confirms that during the crisis, NPLs in Greece increased from 5.7% to 45.4% of total lending, unemployment increased from 7.76% to 26.49%, GDP decreased from 241 billion EUR to 180 billion EUR and there was also deflation.…”
Section: Non-performing Loansmentioning
confidence: 99%